Frequency and prognostic significance of additional cytogenetic abnormalities to the Philadelphia chromosome in young and older adults with acute lymphoblastic leukemia. Issue 1 (2nd January 2018) - Motlló, Cristina; Ribera, Josep-Maria; Morgades, Mireia; Granada, Isabel; Montesinos, Pau; Mercadal, Santiago; González-Campos, José; Moreno, María-José; Barba, Pere; Cervera, Marta; Barrios, Manuel; Novo, Andrés; et al.
Abstract: About 25–35% of adult patients with acute lymphoblastic leukemia show the Philadelphia (Ph) chromosome. Few series have evaluated the prognosis of additional cytogenetic alterations (ACA) to the Ph chromosome. We analyzed the frequency, type and prognostic significance ofACA in adults (18–60 years) treated in the ALL-Ph-08 trial. Fifty-two out of 74 patients (70%) showed ACA and 19 (26%) presented monosomies associated with t(9;22) (monosomal karyotype, MK). Similar complete response (CR) rate, CR duration, overall survival and event-free survival (EFS) were observed in patients with or without ACA, but patients with MK showed shorter CR duration and EFS than the remaining. On multivariate analysis, the only variable with prognostic impact for CR duration and EFS was the presence of MK ( p = .003 and p = .036, respectively). Although ACA associated with the Ph chromosome are frequent, only monosomies were associated with poor prognosis in this group of patients.